Impact of service quality on customer satisfaction in Malaysia airlines: A PLS-SEM approach - Muhammad ShoaibFarooq, Farooq; Maimoona, Salam; Fayolle, Alain; Norizan, Jaafar; Kartinah, Ayupp (Elsevier Ltd, 2018)
This study is aimed to assess the quality of service provided by Malaysia Airlines and its impact on overall customer satisfaction. This study employed a convenience sampling method for collecting data from 460 respondents using a self-administered questionnaire, designed on five dimensions of AIRQUAL scale. Moreover, variance based structural equation modelling (PLS-SEM) was used for testing the proposed structural model. Findings of this study revealed that all five dimensions of AIRQUAL scale i.e. airline tangibles; terminal tangibles; personnel services; empathy and image have a positive, direct and significant impact on customer satisfaction of Malaysia Airlines. This study investigated the impact of service quality dimensions on customer satisfaction in Malaysia Airlines. Due to limited resources and time constraints this study involves respondents from Malaysia Airlines only; for that reason a comparative analysis of findings with other airlines was not possible; therefore it is considered a limitation of this study. Moreover, importance-performance map analysis (IPMA) was also performed for exploring the importance of various dimensions of service quality. Findings indicate that airlines should focus on all dimensions of service quality, with special focus on personnel services and image for enhancing their customer satisfaction. It is expected that findings of this study will help airlines to understand the role of various dimensions of service quality for enhancing their customer satisfaction. © 2017 Elsevier Ltd